Biological complexes bases upon bacterium Pseudomonas fluorenscens and matters of stimulating nature, and their impact on plant growth and development - Solomiichuk, M. (Quarantine and plant protection, 2022)
Goal. The analysis of biocomplex combinations with stimulating nature preparations and different derivative ammonium salts of dihidropirimidine and their efficience study. Methods. The bacterium strain АР-33 Pseudomonas fluorenscens was the researches subject.The biotechnological methods of researches used during the work.The concentration of viable CFU/cm3 determined as per Koch’s method. The preparation efficiency determined at different rate against fungi diseases. The records conducted as generally approved techniques with experimental methods in phytopathology and plant protection. Results.The derivatives of ammonium salts of dihydropirymidine did not show toxic action on concentration decrease of viable cells of bacterium strain АР- 33 Pseudomonas fluorescens. The best weight indexes 100 seeds and quantity of beans forming in soybean showed the combination Planrise — 5 l/ha + 0.1% Xymedon + 0.2% succinic acid solution + 2 ml DMAE + 2 ml DMSO. All biocomplexes combinations showed preparations efficiency against diseases in the scope 59.31—69.63%. The yield increase recorded in 1.15—1.7 times in comparison with control by the results of biocomplexes usage with their fungicide, immunoprotective and stimulating action. The combination Planrise Strain bacterium АР-33 Pseudomonas fluorescens, 3 × 109 CFU/ cm3), 5 l/ha + 0.1% xymedon solution + 0.2% succinic acid solution + 2 ml DMAE + 2 ml DMSO. It was consisted of 3.4 t/ha. The preparation’s efficiency against late blight consisted of 79.1%. Conclusion. All biocomplexes’ combinations usage showed the preparations’ efficiency against diseases in scope 67.3—88.1%. The additional matters DMAE and DMSO (they have influence on transmembrane functions) usage allows to increase preparations efficiency on 8—25% in comparison with combinations without their usage.